Hubungan Sanitasi Lingkungan Dengan Kejadian Stunting Pada Balita Di Desa Ranah Wilayah Kerja UPT Puskesmas Air Tiris Tahun 2023 - Desti, Depni; Harahap, Dewi Anggriani; Mayasari, Endang (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Stunting is a condition of failure to thrive in children due to chronic malnutrition and recurrent infections, especially in the first 1000 days of life (HPK), namely from the fetus to 24 months. The aim of this research was to determine the relationship between environmental sanitation and the incidence of stunting among toddlers in Ranah Village, the UPT working area. Air Tiris health center in 2023. This research is an analytical study with a cross sectional design. The population in this study were all mothers who had toddlers in Ranah Village, the working area of ??the Air Tiris Health Center UPT, namely 155 toddlers. The sample in this study was toddlers using random sampling technique. The data collection tool uses a questionnaire sheet. Data analysis in this study used univariate and bivariate analysis and the Fisher Exact Test. The results of research on unhealthy home environmental sanitation were 19 respondents (17.1%), most of the toddlers experienced stunting in the Stunting category, namely 18 toddlers (16.2%) and there was a significant relationship between environmental sanitation and the incidence of stunting among toddlers at the Air Tiris Health Center in 2023 ( ? value = 0.00). There is a significant relationship between environmental sanitation and the incidence of stunting in toddlers. Unhealthy home environmental sanitation will increase the risk of children suffering from stunting to a greater extent than children from families with healthy home environmental sanitation. So it can be concluded that the main problem of environmental sanitation is improving clean water facilities, healthy latrine facilities and providing rubbish bins.